Fissuras da heteronormatividade: performatividades, violências e relações afetivas - Gregori, Juciane de (2023)
This research aims to analyze the fissures of heteronormativity, present in the performativity and in the social dynamics of violence linked to affective-sexual relations. The field is consolidated from a virtual ethnographic incursion, in the experiences of people who identify themselves as dependent on anonymous love and sex and participate in mutual aid groups around this issue. In this context, this work is consolidated in the midst of a period of intense political instability, as well as being structured during the Covid-19 pandemic situation. Contemplating the fissures and erasures in the binary model of gender and monosexuality of affective relations, it is reflected on heteronormativity and dissident performativity, in which compulsory monogamy, as a dominant configuration of hegemonic bonds of affectivity, is associated with the reproduction of multiple violence. In the violence experienced in the context of affective relationships, heteronormativity presents its discontinuities. Thus, in opposition to the fallacy of equality in the dominant and normative social system, the neoliberal and capitalist policies imposed are contested, not only with regard to gender and sexuality, but also to race, ethnicity, class, corporeality and affections. It is argued that only in this context of exclusionary sociability, it is possible to reproduce experiences such as those listed in the present material. Thus, the epistemological assumptions started from a base of academic production with languages focused on dissent, bringing a bias of stimulus to the intersectional look and notes that intend to arouse interest in decolonial themes. Thus, a qualitative methodology was applied, using technological and digital resources. Employing observation techniques with an emphasis on the density of experiences, a scenario is unveiled that entangled losses, pains, desires, compulsions, isolation, betrayals, in abusive and destructive bonds. Through conflicts in the field of love relationships, which connect to family ties, problematizations about collective and social transformations are provoked, which can resignify the notions of affection and mutual care. In any case, this will only become possible by embracing support networks and promoting alliances that deconstruct the hierarchization of affections, making it possible to nurture other relational bases, in which heteronormativity does not prevail triggers for violations.